2019
DOI: 10.26434/chemrxiv.8143091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wall- and Hybridisation-Selective Synthesis of Nitrogen-Doped Double-Walled Carbon Nanotubes

Abstract: Controlled nitrogen-doping is ap owerfulm ethodology to modify the properties of carbon nanostructures and produce functional materials for electrocatalysis,e nergy conversion and storage,a nd sensing, among others.H erein, we report aw all-and hybridisation-selective synthetic methodology to produce double-walled carbon nanotubes with an inner tube doped exclusively with graphitic sp 2 -nitrogen atoms. Our measurements shed light on the fundamental properties of nitrogen-doped nanocarbons opening the door for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Regarding the N incorporation into the lattice of N-graphene grown on the Cu(111) substrate, Figure 3 b,d shows the core level N 1s spectra where the components below 399 eV recorded straight after the molecular deposition correspond to the nitrilic and pyridinic bonding environments in agreement with the structure of the molecule. 40 On the other hand, after annealing, the N-graphene spectrum is notoriously different. A considerable number of studies reported in the literature have focused on N-graphene, but in seldom cases, both local and bulk sensitive methods have successfully proven to be a N incorporation profile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the N incorporation into the lattice of N-graphene grown on the Cu(111) substrate, Figure 3 b,d shows the core level N 1s spectra where the components below 399 eV recorded straight after the molecular deposition correspond to the nitrilic and pyridinic bonding environments in agreement with the structure of the molecule. 40 On the other hand, after annealing, the N-graphene spectrum is notoriously different. A considerable number of studies reported in the literature have focused on N-graphene, but in seldom cases, both local and bulk sensitive methods have successfully proven to be a N incorporation profile.…”
Section: Resultsmentioning
confidence: 99%
“…A dicyanopyrazophenanthroline C 16 H 6 N 6 molecule was used as C/N feedstock, and its synthesis and capability to induce the incorporation on the graphene network have been reported elsewhere. 40 We have grown N-doped graphene, and its spectroscopic characterization has been carried out in situ in ultrahigh vacuum (UHV) via photoemission spectroscopy (PES) in different energy ranges as explained later, as well as with low-energy electron diffraction (LEED). PES was performed using a dedicated spectrometer equipped with a monochromated Al Kα source (1486.6 eV) and a Scienta RS4000 analyzer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation